The effect of the National Essential Medicines Policy on health expenditures and service delivery in Chinese township health centres: evidence from a longitudinal study. Issue 12 (22nd December 2014) - Zhang, Xin; Wu, Qunhong; Liu, Guoxiang; Li, Ye; Gao, Lijun; Guo, Bin; Fu, Wenqi; Hao, Yanhua; Cui, Yu; Huang, Weidong; Coyte, Peter C
Abstract : Objectives: The government of China has introduced a National Essential Medicines Policy (NEMP) in the new round of health system reform. The objective of this paper is to analyse whether the NEMP can play a role in curbing the rise of medical expenditures without disrupting the availability of healthcare services at township hospitals in China. Design: This study adopted a pre–post treatment-control study design. A difference-in-differences method and fixed-effects model for panel data were employed to estimate the effect of the NEMP. Setting: Chongqing, Jiangsu and Henan Province, in China, in 2009 and 2010. Participants: 296 township health centres. Outcome measures: Outcomes for health expenditures were average outpatient drug expenses per visit, average inpatient drug expenses per discharged patient, average outpatient expenses per visit and average inpatient expenses per discharged patient. Outcomes for care delivery were the numbers of visits per certified doctor per day and the numbers of hospitalised patients per certified doctor per day. Results: The township health centres that were enrolled in the NEMP reported 26% (p<0.01) lower drug expenditures for inpatient care. An 11% (p<0.05) decrease in average inpatient expenditures per discharged patient was found following the implementation of the NEMP. The impacts of the NEMP on average outpatient expenditures and outpatient drug expenditures were not statistically significant at the 5% level. No statistically significant associations were found between the NEMP and reduction in quantity of health service delivery. Conclusions: The NEMP was significant in its effect in reducing inpatient medication and health service expenditures. This study shows no evidence that the quantity of healthcare service declined significantly after introduction of the NEMP over the study period, which suggests that if appropriate matching policies are introduced, the side effects of the NEMP can be counteracted to some degree. Further research including a long-term follow-up study is needed.